Anthocyanin Content, Physicochemical, Nutritional and Sensory Properties of Purple Sweet Potato and Riceberry Biscuits with Rice Bran Organogel - Jaroennon, Pattamaporn; Manakla, Sakunta; Nuanchankong, Jutawan; Lilitchan, Supathra (Journal of Food Health and Bioenvironmental Science, 2023)
Consumers’ awareness on healthful and functional foods has been increasing worldwide. This research aimed to evaluate the anthocyanin content, physicochemical, nutritional, and sensory properties of biscuits prepared from purple sweet potato and riceberry flours. The biscuits were evaluated for their physicochemical properties including color, water activity, moisture contents, and texture profiles. The results showed that the lightness values (L*) ranged from 21.05 to 21.52 with red (a* = 4.97−5.23) and yellow (b* = 0.74−0.84) pigments. The biscuits had the moisture content ranging from 21.72 to 23.70% and the water activity (aw) was within the range that most microorganisms cannot survive (aw = 0.845 to 0.883). Increasing the purple sweet potato flour content in the biscuit formulation resulted in decreased hardness, cohesiveness, springiness, gumminess, and chewiness. All biscuit formulations were analyzed for the nutritional values using the nutritional analysis program. The energies of biscuits ranged from 306.55 to 309.48 kcal. Therefore, the recommended packaging for biscuits was two servings per container. Anthocyanin contents were evaluated using the pH-differential method. The result showed that the formulation with the highest anthocyanin content was formulation P5 (90 purple sweet potato flour: 10 riceberry flour, 66.50±0.99 mg/100g of biscuit). Moreover, formulation P5 also received the highest score in the consumer sensory acceptability test (6.64±1.33). These results suggested that biscuit formulation P5 could be used as a prototype for sweet potato and riceberry flour-based products to promote healthier diet.